Christian Trade Unionism in France: A Left Socialist Experience - Kassalow, E. M. (Relations industrielles / Industrial Relations, 1977)
The author presents a synthesis of the evolution of the Confédération française démocratique du travail. The French Democratic Confederation of Labor.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z